FRI0411 Dual pro-inflammatory and anti-fibrotic role of il-17a in systemic sclerosis skin. (12th June 2018) - Dufour, A.M.; Alvarez, M.; Lemeille, S.; Truchetet, M.-E.; Brembilla, N.C.; Chizzolini, C.
Abstract : Background: Increased levels of IL-17A have been reported in systemic sclerosis (SSc) which role in fibrogenesis is still debated. 1 Furthermore, epithelial cells are preferential targets of IL-17A and recent findings suggest that keratinocytes may participate in dysregulated extracellular matrix homeostasis. 2 Objectives: Our aim was to investigate the interactions between epidermis and dermis in the presence of IL-17A, taking into perspective the fibrotic process. Methods: Primary human keratinocytes were primed with IL-17A and/or TGF-β and conditioned-media were used to stimulate healthy donors (HD) and SSc fibroblasts. Alternatively, organotypic cultures of HD full human skin were challenged with these cytokines. Responses were assessed by quantifying inflammatory mediators and type I collagen (Col-I) levels. The factors produced by keratinocytes were identified by a proteomic approach and their contribution was evaluated by neutralisation assays. Changes in gene expression in full human skin after treatment with IL-17A and/or TGF-β were analysed by RNA sequencing (RNA-seq). Results: Unstimulated HD- and SSc-derived keratinocyte-conditioned media (KCM) promoted collagen production by fibroblasts to a similar extent and in a dose-dependent manner. Cytokine array analysis and neutralising assays showed that TGF-β was, at least in part, responsible for the pro-fibrotic effect of KCM. Priming of keratinocytes with IL-17A directly decreased Col-I production and significantly reduced Col-I induced by TGF-β both in SSc and HD fibroblasts. In full human skin, IL-17A promoted pro-inflammatory responses by inducing 2- to 4-fold increase of IL-8, IL-6, MCP-1 and MMP-1 levels, while showing direct anti-fibrotic effects, as well as decreasing by 2-fold collagen production triggered by TGF-β (p=0.02). RNA-seq revealed that TGF-β induced the expression of many collagen genes, while this was not the case for IL-17A. However, IL-17A promoted a pro-inflammatory signature in the skin and strongly downregulated expression of serpin family members, known to be involved in fibrogenesis. Conclusions: Keratinocytes profoundly influence dermal fibroblast responses, which are further modulated in the presence of IL-17A. These data support a role for keratinocytes in the pathogenesis of SSc. IL-17A acts as a potent anti-fibrotic factor in the model of keratinocyte – fibroblast interactions, as well as in the full human skin, promoting pro-inflammatory and anti-fibrotic responses. References: [1] Truchetet ME, et al. Arthritis & Rheumatol2013;65:1347–56. doi:10.1002/art.37860 [2] Takahashi T, et al, J Exp Med. 2017Feb 23. doi:10.1084/jem.20160247 Acknowledgements: Work supported in part by grant 310030–1 59 999 from the Swiss National Science Foundation to CC. Disclosure of Interest: None declared